Investigation of the relationship between joint position sense acuity and postural stability during stance - Gan Mingxuan (2014)
ABSTRACT Postural stability is important as it greatly influences our ability to perform daily activities safely. Reduced in stability, usually seen in elderly increased the risk in falling. This is very undesirable as an elderly will take a longer time to recover as compared to younger adults and children.